The Association Between Particulate Air Pollution and Respiratory Mortality in Beijing Before, During, and After the 2008 Olympic and Paralympic Games - Breitner, Susanne; Su, Chang; Franck, Ulrich; Wiedensohler, Alfred; Cyrys, Josef; Pan, Xiaochuan; Wichmann, H-Erich; Schneider, Alexandra; Peters, Annette (Frontiers in Environmental Science, 2021)
To improve ambient air quality during the 2008 Summer Olympic and Paralympic Games, the Chinese Government and Beijing's municipal government implemented comprehensive emission control policies in Beijing and its neighboring regions before and during this period. The goal of this study was to investigate the association between particulate air pollution and cause-specific respiratory mortality before, during and after the period of the Olympic Games. Further, we wanted to assess whether changes in pollutant concentrations were linked to changes in respiratory mortality. We obtained daily data on mortality due to respiratory diseases (coded as J00-J99 according to the International Classification of Diseases and Related Health Problems 10th revision [ICD10]) and pneumonia (ICD10: J12-18), meteorology, particulate matter less than 10µm or 2.5μm in diameter (PM10, PM2.5) and particle number size distribution from official monitoring networks and sites located on the Peking University campus between May 20 and December 1, 2008. We assessed the effects of particulate air pollution on daily respiratory mortality using confounder-adjusted Quasi-Poisson regression models. Furthermore, we estimated air pollution effects for three periods - before (May 20 to July 20, 2008), during (August 1 to September 20, 2008) and after (October 1 to December 1, 2008) - by including interaction terms in the models. We found associations between different particle metrics and respiratory and pneumonia mortality, with more pronounced effects in smaller particle size ranges. For example, an interquartile range increase of 7,958 particles/cm3 in ultrafine particles (particles <100 nm in diameter) led to a 16.3% (95% confidence interval [CI]: 4.3%; 26.5%) increase in respiratory mortality with a delay of seven days. When investigating the sub-periods, results indicate that a reduction in air pollution during the Olympics resulted in reduced (cause-specific) respiratory mortality. This reduction was especially pronounced for pneumonia mortality. The findings suggest that even a short-term reduction in pollution concentrations may lead to health benefits and that smaller particles in the ultrafine size range may be particularly important for respiratory health.